Irregularidad superficial del pavimento y su influencia en el consumo de combustible y emisiones en la ciudad de Barranquilla (2020)
In the present investigation, the influence that the surface irregularity of a pavement has in terms of the International Roughness Index - IRI on fuel consumption and gas emissions into the atmosphere generated by typical vehicles in the city of Barranquilla was analyzed. The research included a literary review on the models for calculating fuel consumption and on the characteristics of the pavement that influence fuel consumption, within these characteristics they determined the roughness, macro-texture and slip resistance of the pavement. The calculation of fuel consumption and emissions with respect to IRI was carried out for three different typical vehicles of the road network of the city of Barranquilla. The results show that a measure that increases the IRI value increases fuel consumption and gas emissions into the atmosphere. In addition, the heavier vehicles you have, the higher the fuel consumption and gas emissions. On the other hand, it was determined that the highest gas emissions (grams / km) from vehicles correspond to carbon dioxide CO2 and nitrous oxide NOx, which are gases that increase the phenomenon of global warming. The results of this article in terms of fuel consumption and emissions may be used in future research and projects that are developed in the urban environment of the city of Barranquilla AND for any main city in Colombia.